Inorganic source of selenium in the culture of calluses of Catharanthus roseus (L.) - Terreros-Rosales, Luis Guillermo; Castañeda-Nava, José Juvencio; León-Morales, Janet María; García-Morales, Soledad (Revista Mexicana de Ciencias Agrícolas, 2024)
Catharanthus roseus (L.) is a species with high pharmaceutical and ornamental value, which has led to the search for biotechnological alternatives to improve the establishment of cell cultures. This work aimed to induce callus formation in different explants of C. roseus and to evaluate the effect of two inorganic sources of selenium (Se) on their growth in order to identify the best range of concentrations. Callus formation was induced from hypocotyls and leaves, evaluating three different culture media. To increase the biomass production of C. roseus calluses, sodium selenite (Na2SeO3) and sodium selenate (Na2SeO4) were used as inorganic sources of Se. Callus induction and growth assessment were performed in 2022. Concentrations of 1, 5, 10, 15, 20, 50, and 100 mg L-1 of both compounds were tested in two independent experiments. Treatments with 1, 5, and 10 mg L-1 of Na2SeO3 and Na2SeO4 produced friable calluses with higher fresh weight. The source of Se influenced the growth of calluses; a fresh weight of 0.52 g was obtained with 1 mg L-1 of Na2SeO4, higher than that obtained with the same concentration of Na2SeO3. Concentrations greater than 20 mg L-1 from both sources negatively affected callus growth.